Analysis of Strategy and Implementation of the Adiwiyata Program Based on Local Wisdom to Improve Environmental Literacy in Asahan Regency - Lubis, Suriati; Johari, Asni; Siburian, Jodion; Yelianti, Upik (Universitas Pahlawan Tuanku Tambusai, 2025)
The Adiwiyata program as an environmental education initiative in Indonesia, aims to improve environmental literacy through a school-based approach. This literature review analyzes 25 articles relevant to the strategy and implementation of the Adiwiyata Program, with a focus on integrating local wisdom to improve environmental literacy. The articles use a variety of research methods, including qualitative, quantitative, mixed method, and systematic literature reviews. The results of the study show that the Adiwiyata Program is effective in increasing awareness, knowledge, and attitudes of caring for the environment, although there are limitations such as generalization of findings and lack of deep integration of local wisdom. This review identifies the strengths, shortcomings, and novelties of previous research, and recommends strategies based on local wisdom to strengthen environmental literacy in Asahan Regency.